THE ROLE OF ISLAMIC FINANCIAL INCLUSION IN POVERTY, INCOME INEQUALITY, AND HUMAN DEVELOPMENT IN INDONESIA - Novreska, Sasiaprita; Arundina, Tika (Journal of Islamic Monetary Economics and Finance, 2024)
This study empirically analyses the role of Islamic financial inclusion in overcoming poverty, income inequality, and human development problems by employing yearly panel data of 33 provinces in Indonesia from 2014 to 2022. The results show that, except Aceh and DKI Jakarta, all provinces in Indonesia have low Islamic Financial Inclusion Index (IFII). Our analysis reveals that Islamic financial inclusion exerts significant roles in poverty reduction and human development improvement, while it is insignificantly related to income inequality. During the Covid-19 pandemic, the effect on human development of financial inclusion is further strengthened. We further note that the effects of Islamic financial inclusion depends on the levels of Human Development Index (HDI), where poverty reduction and human development improvement are apparent only in provinces with high and very high HDI.